Unveiling the Microfoundations of Absorptive Capacity: A Study of Coleman's Bathtub Model. (May 2019) - Distel, Andreas P.
Although the concept of absorptive capacity has gained wide acceptance in the literature, our understanding of the origins of a firm's ability to absorb and leverage new knowledge is limited. Drawing on Coleman's (1990) bathtub framework for macro-micro-macro-relations in social science, this study explores the multilevel antecedents of absorptive capacity using survey data gathered from 342 informants at different levels of analysis in 106 medical technology firms. Multilevel structural equation modeling analyses indicate that formal and informal integration mechanisms are positively related to absorptive capacity at the organizational level and that this relationship is mediated through a microlevel process. The findings reveal that knowledge workers' cognitive process of perspective taking and their creative behavior are important microfoundations of absorptive capacity. Moreover, the results emphasize the critical role of key employees in explaining firm-level heterogeneity in building organizational capabilities.